(untitled) (Dhaka University Journal of Biological Sciences, 2017)
Aluminium (10 to 150 μM) decreased K+ accumulation in the root and shoot of rice and the root, stem and leaves of chickpea seedlings. On the other hand, Al, at a concentration of 10, 50, 100 and 150 μM increased Na+ content in different parts of rice and chickpea seedlings. 150 μM Al increased Na+ accumulation in the root by 2.1‐ to 2.2‐folds from 3 to 96 hrs of treatment. Aluminium at a concentration of 150 μM caused a dramatic 2‐ and 3.4‐folds increase in Claccumulation in the root and shoot of rice, respectively. In chickpea, 150 μM Al increased Cl‐ accumulation in the root by 2‐folds. On the contrary, Al application decreased NO3‐ accumulation in different parts of rice and chickpea seedlings. Dhaka Univ. J. Biol. Sci. 26(2): 141-149, 2017 (July)